SISTEM REKRUITMEN DAN KADERISASI PARTAI KEADILAN SEJAHTERA DI JAWA BARAT - Dede Anggy Reynaldin (Universitas Jenderal Ahmad Yani, 2018)
This research entitled “the system of Recruitmen and the prosperous justice party cadre recruitment in West Java”. The real problem in this research not yet optimal recruitment and cadre recruitment system which applied the PKS in West Java, as seem fro, the existence of a decrease in the percentage of the vote in legislative elections West Java, so the researchers took factors influencing the process of cadre recruitment patterns according to Harun who are institutional, cadre recruitment patterns, quality and time. As for the identification of the problem as follows : (1). How the system of recruitment and the Prosperous Justice Party cadre recruitment in West Java?, (2). What are the Factors that inhibit recruitment and cadre recruitment system in the Prosperous Justice Party in West Java?, (3). Any efforts to overcome barriers in the system of recruitment and the Prosperous Justice Party cadre recruitment in West Java? In this study, researchers used a descriptive research methods wit qualitative approaches. The techniquw of data collection was done through literature study, observation and interview key informants in depth with DPW PKS West Java, and the informants supporters chairman of cadre recruitment and PKS cadre. Determination of informants/purposive sampling done in a resource that is chosen with consideration and specific purpose. While the main instrument in the study are researchers themselves. Based on the result of the study showed : (1). Recruitment and cadre recruitment pattern have not been implemented optimally so that the need for renewal in the methods of recruitment and cadre recruitment conducted by the Prosperous Justice Party in West Java. (2) The role of the instituations existing in the PKS cadre recruitment namely recruitment of members through Dakwah movement in various walks of the life by means of an intensive approach towards prospective. (3). Phasing in any cadre recruitment agenda is a method to improve the quality of cadres of the the PKS candidate in West Java. (4). The PKS used the system semester in each recruitment agenda and cadre recruitment. (5). There are barriers that exist in the system of recruitment and the PKS cadre recruitment. (6). Efforts continue to be made to overcome existing barriers.